Performance measures and factors influencing the performance of Seaport Container Terminal's operation efficiency : The case on Northbutterworth Container Terminal (NBCT) - Lingam, Ramachandran (2014)
In the world today, all ports are unique and the tasks to measure and analyse the performance is not so easy. It becomes more difficult when a port failed to identify the measurements or indicators in determining the overall performance of the container port. This study aims to identify measures or indicators used by the North Butterworth Container Terminal (NBCT) to measure the performance of operations and the second purpose is to identify the factors influencing the performance of NBCT in determining its operational efficiency. This was a qualitative study with face to face interview and observation with experts‟ persons related to Operation, Container Yard, and Statistic and Quality & Syariah Department of NBCT. The findings from the interview and observation method, have identified there are four type of Performance Indicators (PI) is being used by NBCT namely are measure of production, a measure of productivity, utilization measurement, and services measurement. The findings of this study have shown that the performance achievement of NBCT for the year 2013 was lower than targeted performance because of the internal and external factors which have influenced the performances such as sets high performance targets especially for targeted total handles TEUs, lack of workforce in the terminal is a main reason to non-achievement of the targets, and less availability of new advanced technology equipment, less supports from the management. As a summary, the internal and external factors have influenced to the drop of the operation‟s performance in NBCT.